An Ottoman century : the district of Jerusalem in the 1600s - Zeʼevi, Dror, 1953- (SUNY series in medieval Middle East history., 1996)
"Based on micro-level research of the District of Jerusalem, this book addresses some of the most crucial questions concerning the Ottoman empire in a time of crisis and disorientation: decline and decentralization, the rise of the notable elite, the urban-pastoral nexus, agrarian relations and the encroachment of European economy. At the same time it paints a vivid picture of life in an Ottoman province. By integrating court record, petitions, chronicles and even local poetry, the book receates a historical world that, though long vanished, has left an indelible imprint on the city of Jerusalem and its surroundings."--Book cover